Poria Attenuates Idiosyncratic Liver Injury Induced by Polygoni Multiflori Radix Praeparata - Gao, Dan; Pang, Jing-Yao; Zhang, Cong-En; Li, Chun-Yu; Tu, Can; Zhang, Hai-Zhu; Niu, Ming; Xiong, Yin; Xiao, Xiao-He; Zhao, Kui-Jun; Gao, Wei-Wei; Wang, Jia-Bo (Frontiers in Pharmacology, 2016)
The hepatotoxicity induced by Polygoni Multiflori Radix Praeparata (PM) has been worldwide reported. Hence, it is worthwhile to find herbs with detoxification based on the compatibility of traditional Chinese medicine. In this work, rat model with PM/LPS-stimulated idiosyncratic liver injury was used. The effects of Poria, Licorice and Panax notoginseng on rats of PM/LPS-induced liver injury were investigated, respectively, hoping to find the most effective herbal medicine to reduce the hepatotoxicity. The biochemical and histological tests showed that PM induced the idiosyncratic hepatotoxicity of rats with modest inflammation triggered by non-injurious dose of LPS. We found that the combined use of Poria and PM in the ratio of 1:2 could significantly ameliorate the PM/LPS-induced liver injury and systemic inflammation. Furthermore, UPLC/QTOF-MS-based metabolomics was performed to identify possible biomarkers and underling biological pathways. Ten metabolites were expressed differentially among LPS, PM/LPS and detoxification-treated groups by PCA and OPLS-DA analysis, which could be potential biomarkers. MetaboAnalyst and pathway enrichment analysis revealed that alterations of these metabolites were primarily involved in three pathways: arginine and proline metabolism, primary bile acid biosynthesis and sphingolipid metabolism. This research provides systematic experimental basis for the hepatoprotective effects of Poria against PM/LPS-induced liver injury for the first time, and these findings may help better understand the mechanisms of underlying pathophysiologic processes.